Optical solitons of (3+1) dimensional and coupled nonlinear Schrodinger equations - Inan, Ibrahim Enam; İnç, Mustafa; Rezazadeh, Hadi; Akinyemi, Lanre (Springer, 2022)
In this paper, we implemented extended exp(-phi(xi))-expansion method for some exact solutions of (3 + 1)-dimensional nonlinear Schrodinger equation (NLSE) and coupled non-linear Schrodinger's equation. The solutions we obtained are hyperbolic, trigonometric and exponential solutions. We observed that these solutions provided the equations through Mathematica 11.2. Apart from that, we have shown the graphics performance of some of the solutions found. This method has been used recently to obtain exact traveling wave solutions of nonlinear partial differential equations. The results achieved in this study have been confirmed with computational software Maple or Mathematica by placing them back into NLFPDEs and found them correct. We posited that the approach is updated to be more pragmatic, efficacious, and credible and that we pursue more generalized precise solutions for traveling waves, like the solitary wave solutions.
Keywords: (3+1)-dimensional NLSE; Coupled NLSE; Extended -expansion method; Exact solutions